Analysis of the Ability to Pay for Disaster Insurance Program - Siswanto, Adrianus Dwi (Badan kebijakan Fiskal, 2014)
Indonesia is disaster-prone countries. Then the disaster mitigation and adaptation, with insurance as one available option, need to be considered. Insurance scheme can be applied as an alternative to allocate the burden of disaster cost, not only to government and households but also to insurance companies. This study examines the ability to pay of the households for the insurance program in different provinces using the data of the Survei Sosial Ekonomi Nasional (Susenas] for the year 2010. The result is there are some provinces with high vulnerability index but low ability to pay for insurance expenses; and vice versa. Potential spending on average for catastrophe insurance is at 2.8 percent i.e. the portion of household expenditures that potentially. can be allocated to disaster premium insurance payments.